Development of Augmented Reality-Based Flashcard Learning Materials to Enhance Students’ Critical Thinking Skills in the Human Body Systems Curriculum - Alfina Alfina; Lalu Zulkifli; AA Sukarso; Jamaluddin Jamaluddin; Irawan Zain Irawan Zain (LPPM Institut Pendidikan Nusantara Global, 2026)
21st-century education demands the use of learning media that is more adaptive, creative, and interactive, especially in visualizing abstract concepts. This study aims to investigate the urgency and outcomes of developing Augmented Reality (AR)-based flashcard learning media on the topic of the Human Body’s Organ Systems to enhance the critical thinking skills of elementary school students. This research employs the Research and Development (R&D) method using the ADDIE development model. Based on a needs analysis conducted through observation and interviews at SDN 2 Rumak, it was found that the limitations of conventional media cause students to struggle with visualizing the details of organs and their functions, thereby hindering the development of critical thinking. The AR-based flashcard media developed using the Assemblr EDU platform is capable of presenting interactive 3D models that allow students to observe objects from various angles in real-time. Research findings indicate that this media meets the criteria for high validity, with a 93% approval rate from subject matter experts and 90% from media experts. The practicality of the media, as assessed based on teacher and student response instruments, reached an average 89.5% (very practical), supported by the app’s ease of navigation and ergonomic card design. Additionally, an effectiveness test using an N-Gain score of 0.72 indicates an improvement in students’ critical thinking skills in the “High” category. Therefore, the development of technology-based learning tools such as AR flashcards is crucial as an innovative solution for visualizing complex material and improving the quality of basic education in Indonesia.